DESIGN OF STRUCTURE AND KINEMATIC LAYOUT OF PARTS OF MECHANISM WITH ROTATING CYLINDERS (Perner's Contacts, 2019)
The paper deals with the constructional design of kinematic arrangement of mechanism with rotating cylinders and its use especially in piston combustion engines (spark-ignition engine and diesel engine), which may be two or four-stroke engines. The entire mechanism will be designed with the aim to completely eliminate the side (normal) force acting on the piston by ensuring a zero angle of connecting rod swing β at each mechanism position. This will be ensured by connecting rod’s kinematics – it should only be moved in the cylinder axis.
Keywords: kinematics; design; rotating cylinders